Application of New Polymer Composite Materials in Rock Slope Ecological. Issue 4 (October 2021) - Huang, Wei; Lin, Ke; Du, Jiaxin; Zhou, Cuiying; Liu, Zhen; Zhang, Lihai
Abstract: Geological disasters frequently occur in red bed areas. Ecological protection can improve the stability of the rock slope and beautify the environment and reduce soil erosion. The natural red bed weathered soil often has a loose structure and poor water retention, resulting in poor vegetation growth. It is necessary to develop a new material to improve the slope soil and promote plant growth. Therefore, this study employed the self-developed ADNB soil stabilizer to improve the silty clay in the red bed areas. The effects of ADNB on soil physical properties (density, moisture content, and temperature) and ecological properties (germination rate, plant height, and coverage) were analyzed to examine the effects of ADNB on soil improvement. The results show that, compared with natural soil, the density of ADNB treated soil decreased by 9.1%−14.3%, water content increased by 9.3%−19.7%, water holding capacity increased by 20.0%−33.3%, temperature increased by 0.7%−1.8%, germination rates of herbs and shrubs increased by 3.0%−36.0%, and 1.0%−17.0%, respectively, plant height increased by 8.7%−98.6%, and coverage increased by 25%−45%. This study provides theoretical and data support for slope ecological protection and soil erosion control in red bed areas.